Produção por aspersão térmica de revestimentos amorfos resistentes à corrosão e ao desgaste utilizando a liga Fe60Cr8Nb8B24 - Koga, Guilherme Yuuki (2014)
Metallic coatings are generally designed to confer high wear and corrosion resistance to the substrate to be coated. These properties are essential to make structures suitable to resist to aggressive environment and operating conditions. In this context, Fe-based alloys have drawn great attention due to their unique physical and chemical properties and relatively low cost of iron. Compared with traditional crystalline metallic materials, Fe-based amorphous alloys exhibit high strength, hardness and superior corrosion resistance, attributed to their disorder structures as well as chemical homogeneity. Powder alloys can then be used to produce amorphous coatings on steel substrate, improving corrosion and wear properties in aggressive environments. This work reports on the production of high corrosion and wear resistant coatings produced by HVOF (High Velocity Oxygen Fuel) using only commercials precursors. Initially, preliminary studies were made for the evaluation of glass forming ability (GFA) for the selected Fe60Cr8Nb8B24%at. composition. Further analyses of the crystallization of fully amorphous samples were conducted to correlate the crystalline phases with the physical and chemical properties. Then, the production of amorphous coatings was studied. The microstructure of the samples was characterized by optical microscopy (OM), confocal microscopy (CM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and differential scanning calorimeter (DSC). Corrosion, wear and hardness tests were performed as well as porosity and oxygen content measurements. The results have shown the feasibility of production of high quality coatings by HVOF (low porosity and oxygen content together with high hardness and large amount of amorphous fraction). However, the corrosion properties of the coatings were found to be impaired by the presence of α-Fe and FexB (x=1,2 and 3) crystalline phases.